2012
DOI: 10.2478/v10289-012-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Strength of Honey Bee Colonies (Apis mellifera) Supered in Different Ways on Maximizing Honey Production in Nepal

Abstract: S u m m a r yA study was carried out to investigate the effect of the original strengths of honey bee colonies supered in different ways, on the production of honey by Apis mellifera bees in the Terai region of Nepal. Bee colonies of three different original strengths, in which the bees covered 5, 10 and 20 combs, were supered in three different methods. The results showed that honey production was highly correlated to the number of worker brood cells in the colonies (r = 0.96, p = 0.003). Colonies of 5 comb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…The pattern of pollen hoarding was almost similar in all the honey extraction frequencies while their interactions with dates of observations were non-significant. In similar kind of experiments, Berry et al (2000) ; Allsopp (1994); Neupane et al (2012) and Saini et al,2018a found superiority of pollen area in high strength colonies.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The pattern of pollen hoarding was almost similar in all the honey extraction frequencies while their interactions with dates of observations were non-significant. In similar kind of experiments, Berry et al (2000) ; Allsopp (1994); Neupane et al (2012) and Saini et al,2018a found superiority of pollen area in high strength colonies.…”
Section: Resultsmentioning
confidence: 82%
“…(1992); Szabo and Sparns (1994); Berry et al (2000) and Allsopp (1994). Neupane et al (2012) found honey production to be highly correlated to the number of worker brood cells in the colonies (r = 0.96, p = 0.003). They found initial colony strength of 5, 10 and 20 combs (ratio 1:2:4) resulted in overall mean number of brood cells at the rate of 1.0:1.4:1.8, thus, in proportion to the strength of colonies, the lowest increase of the brood amount occurred in strong colonies.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Nelson and Gary (1983), honey production is correlated positively with queen weight. Colony strength of honey bees has been found to be one of the most important factors for maximizing honey production (Neupane et al, 2012). Weiss (1971Weiss ( , 1983 found no difference in honey production by colonies headed by queens reared from eggs or 1.5-day-old larvae.…”
Section: Discussionmentioning
confidence: 99%
“…• In-hive products: studies show the positive correlation between the number of worker bees in a colony and the amount of honey produced (Neupane et al, 2012;Gąbka, 2014).…”
Section: Effectsmentioning
confidence: 99%